2014
DOI: 10.5530/pc.2014.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Thai medicinal plants against beverage spoilage microorganisms and their potential in retarding Alzheimer’s disease progression

Abstract: Thai medicinal plants (34 crude methanolic extracts) were tested for their antimicrobial activities, antiacetylcholinesterase and antioxidant activities, total phenolic and flavonoid contents. Acorus calamus, Cassia alata, Crocus sativus, Nymphaea lotus and Phyllanthus emblica extracts showed strong antimicrobial activity against spoilage yeasts, lactic acid bacteria and acetic acid bacteria tested. Most susceptible yeast strains were Rhodotorula glutinis and Schizosaccharomyces pombe. Kaempferia parviflora, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Thai herbs, fruits and vegetables are a major source of natural antioxidants such as polyphenol (phenolics, flavonoids), vitamin C and other compounds [10,11]. Some Thai local plants including fruits of Indian gooseberry (Phyllathus emblica) [11,12] and black rice (Oryza sativa) [13], fruit peels of mangosteen (Garcinia mangostana) [14], and leaves of lopea tree (Acanthopanax trifoliatus) [15] were reported to have very high phenolic content and strong antioxidant activity. So far, only few plants with strong anti-diabetic and anti-acetylcholinesterase activities have been reported [12,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thai herbs, fruits and vegetables are a major source of natural antioxidants such as polyphenol (phenolics, flavonoids), vitamin C and other compounds [10,11]. Some Thai local plants including fruits of Indian gooseberry (Phyllathus emblica) [11,12] and black rice (Oryza sativa) [13], fruit peels of mangosteen (Garcinia mangostana) [14], and leaves of lopea tree (Acanthopanax trifoliatus) [15] were reported to have very high phenolic content and strong antioxidant activity. So far, only few plants with strong anti-diabetic and anti-acetylcholinesterase activities have been reported [12,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Some Thai local plants including fruits of Indian gooseberry (Phyllathus emblica) [11,12] and black rice (Oryza sativa) [13], fruit peels of mangosteen (Garcinia mangostana) [14], and leaves of lopea tree (Acanthopanax trifoliatus) [15] were reported to have very high phenolic content and strong antioxidant activity. So far, only few plants with strong anti-diabetic and anti-acetylcholinesterase activities have been reported [12,[16][17][18]. For instance, Alium sativum (garlic) bulbs [19], Ginkgo biloba leaves [19], Terminalia chebula fruits [5], Aloe vera leaves and Morinda citrifolia barks/leaves [16] have good anti-diabetic effect, while Stephania pierrei tubers [18] and Nelumbo nucifera (lotus) petals [12] have strong anti-acetylcholinesterase activity.…”
Section: Introductionmentioning
confidence: 99%
“…This synergism is often demonstrated by the antioxidant activity of the mixture, which is greater than the sum of the antioxidant activity of the single active compound molecule [4]. Myrabolan wood fruits, Indian gooseberry fruits, and gambir extracts were reported to possess very strong antioxidant activity with the EC 50 of 387.23, 490.47 and 478.71 µg extract/mg DPPH by DPPH radical scavenging assay [17]. Anggraini et al [19] also revealed strong antioxidant activity of gambir extracts.…”
Section: Discussionmentioning
confidence: 99%
“…This compound was synthesized when plants are attacked by pathogens [33]. Moreover, crude methanolic extracts of black galingale rhizomes, sacred lotus petals, serpentine roots and asiatic pennywort leaves at 1 mg/mL were reported to possess strong acetylcholinesterase inhibitory activity (more than 70% inhibition), whereas the extracts of gingko (G. biloba) leaves, saffron pollens and blue pea flowers at 1 mg/mL were found to exhibit 32.73, 29.21 and 25.55% acetylcholinesterase inhibition, respectively [17]. Ingkaninan et al [34] reported that methanolic extract of sacred lotus stamen had 23.77% acetylcholinesterase inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation